A cytoderm metabolic labeling TPAPy-Tre for real-time detection of vitality of Mycobacterium tuberculosis in sputum - Mengru Yang; Guiqin Dai; Dan Li; Pengfei Zhao; Senlin Zhan; Hongjuan Qin; Hongzhou Lu; Mingbin Zheng; Peize Zhang (Microbiology Spectrum)
ABSTRACT Early bactericidal activity is a vital measure in developing new tuberculosis (TB) drugs. Traditional methods, including colony-forming units (CFUs) and time to positivity (TTP), have limitations. This study aimed to evaluate the efficacy of TPAPy-Tre fluorescence microscopy in monitoring early therapeutic responses compared with conventional culture methods in patients with pulmonary multidrug-resistant/rifampicin-resistant TB. In an open-label clinical trial at the Third People’s Hospital of Shenzhen, China, seven sputum smear-positive patients aged ≥18 years were enrolled. Sputum samples were consecutively analyzed using solid and liquid cultures and TPAPy-Tre microscopy. The study found that TPAPy-Tre fluorescence intensity significantly decreased from 271.5 (95% confidence interval [CI], 177.4–365.7) before treatment to 142.8 (95% CI, 104.7–180.9) after treatment (P < 0.05). TPAPy-Tre results strongly correlated with CFU (Spearman ρ = 0.60; 95% CI, 0.35–0.77; P < 0.001) and TTP (Spearman ρ = −0.33; 95% CI, −0.56 to −0.04; P < 0.05). Among selected participants, the median fluorescence intensity decreased from 51.5 (interquartile range [IQR], 39.0–63.6) to 13.2 (IQR, 7.8–20.0) after treatment (P < 0.001). TPAPy-Tre shows potential as a rapid, visual method for tracking bacterial vitality during TB treatment, offering immediate feedback on treatment response. These results support its use alongside conventional methods in clinical settings, though larger studies are needed for further validation.IMPORTANCEEarly bactericidal activity (EBA) is an important tool in clinical studies in the development of new tuberculosis drugs. Current traditional methods of efficacy monitoring present significant limitations. There is a need for novel and efficient tools to monitor treatment response in real-time when EBA is performing.